Extravasation of antineoplastic agents in an Oncological Center (Research, Society and Development, 2021)
Introduction/Objective: This retrospective cross-sectional cohort study analyzed the extravasation index of antineoplastic therapy agents, demographic and clinical data. Methods: Seventy-six patients were evaluated in the period between 2017-2019. The project was approved by the Research Ethics Committee of a Brazilian Foundation. Results: In 72 months, 105,890 applications were administered, of which the incidence rate of extravasation of antineoplastic agents was 0.071%. Patients (N=311) selected for this study had a mean age of 55.42 years and a median age of 57. The most frequent diagnoses were breast cancer (11.66%), ovarian cancer (10%), colon cancer (8.33), rectal cancer (8.33) and uterine cancer (8.33%). The main variables that presented a significant impact with p